Assessment-based Pest Management of German Cockroaches - Faith Oi; Emma N. I. Weeks; J Jonovich; D. Miller (EDIS, 2018)
Assessment-based pest management emphasizes the importance of evaluating the intensity of a pest problem before treating the problem. This 10-page fact sheet written by F.M. Oi, E. Weeks, J. Jonovich, and D. Miller and published by the UF/IFAS Entomology and Nematology Department explains the strategy and includes a decision flow chart to provide an easy-to-follow overview on how a German cockroach problem can be assessed and successfully managed with specific guidance for each of four levels described in the fact sheet. The levels described constitute an escalation protocol that may approximate the tiers in a LEED (Leadership in Energy and Environmental Design) pest-management plan and may meet the requirements of some “green” pest-management certification programs, depending on level. http://edis.ifas.ufl.edu/in1190